Ctrl + Class: A Phenomenological Unfurling of the Lived Digital Leap of the 21st Century Teachers - Princes Joy G. Arambala; J. P. Versinie M. Salmorin (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
This study is relevant to the academic community as it provides insights into the lived experiences of faculty members navigating technology-enhanced learning (TEL) in a private Catholic institution. It presents primary data gathered through in-depth interviews with four faculty participants from Holy Cross of Davao College, Region XI, Philippines. Understanding these experiences can help educators and institutions develop more effective strategies for integrating digital tools in faith-based educational settings. This qualitative study employed a phenomenological approach to explore how teachers perceive, adopt, and utilize technology in their classrooms. Using purposive sampling, the researchers chosen participants who actively implemented TEL. Thematic analysis revealed that faculty members experienced both growth and challenges in their digital journey. They expressed fulfillment when students engaged more deeply through tools like Padlet and Edpuzzle, but also shared frustrations due to infrastructure limitations and evolving digital platforms. Participants described coping mechanisms such as self-learning, peer mentoring, and strategic use of tools like Google Classroom and Canva. Their insights emphasized the importance of adaptability, reflective practice, and a student-centered mindset. The study recommends institutional support for professional development, improved infrastructure, and collaborative efforts to foster inclusive and effective digital learning environments.